2023
DOI: 10.1097/qad.0000000000003556
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal accumulation of hyperphosphorylated tau protein predicts stable memory impairment in people living with HIV

Abstract: Objectives:As lifespans increase in people with HIV (PWH), there is concern that age-related neurodegenerative disorders may contribute to cognitive decline. We asked whether brain accumulation of Alzheimer's disease (AD)-associated proteins amyloid-beta (Aβ) and hyperphosphorylated tau (p-tau) predicted cognitive performance in middle-aged PWH.Methods:In a prospectively followed, cognitively-characterized autopsy sample of 135 PWH, we used immunohistochemistry to assess Aβ plaques and neuronal p-tau in medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The association of total Tau levels with HIV or HAND remains controversial. Some studies reported an increased deposition of aggregated Tau in brain [ 61 ] or increased Tau in CSF [ 62 , 63 , 64 ], whereas others found no significant difference [ 19 , 27 , 65 ]. Further studies are needed to determine the specificity and diagnostic significance of Aβ and Tau biomarkers in PWH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of total Tau levels with HIV or HAND remains controversial. Some studies reported an increased deposition of aggregated Tau in brain [ 61 ] or increased Tau in CSF [ 62 , 63 , 64 ], whereas others found no significant difference [ 19 , 27 , 65 ]. Further studies are needed to determine the specificity and diagnostic significance of Aβ and Tau biomarkers in PWH.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a nonspecific marker that reflects axonal injury in many neurological disorders. β amyloid (1–42) (Aβ42) aggregates and hyperphosphorylated Tau-containing neurofibrillary tangles are hallmarks of AD that are detected in the brains of some older PWH [ 17 , 18 , 19 , 20 ]. An increased CSF Tau/Aβ42 ratio is a biomarker associated with risk of aMCI and AD; increased CSF Tau reflects its release from degenerating neurons while decreased CSF Aβ42 reflects higher amyloid deposition in the brain [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HIV‐associated neurocognitive disorders (HAND) in PLWH ranges from 19% to 52% in developed countries (Atashili et al., 2013 ; Lawler et al., 2010 ), and 14% to 64% in developing countries (Debalkie Animut et al., 2019 ; Lawler et al., 2010 ). Accumulating evidence suggests that common pathways and factors are modulated in the brains of HIV + and Alzheimer's disease (AD) patients, thus pointing out similarities and convergence of these two pathologies (Achim et al., 2009 ; Chai et al., 2017 ; Esiri et al., 1998 ; Garces et al., 2023 ; Gelman & Schuenke, 2004 ; Gonzalez et al., 2023 ; Green et al., 2005 ; Izycka‐Swieszewska et al., 2000 ; Kim et al., 2013 ; Meehan et al., 2023 ; Nebuloni et al., 2001 ; Raja et al., 1997 ; Stern et al., 2018 ; Xu & Ikezu, 2009 ). As regards the development of Alzheimer's‐like pathology in older HIV + survivors, it remains unclear whether the disease develops independently or as a comorbidity of HIV‐1.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are conflicting reports demonstrating no correlation between the levels of cerebrospinal fluid (CSF) Amyloid beta (Aβ 42) and the deposition of fibrillary brain amyloids assessed by magnetic resonance imaging (MRI) using Pittsburgh Compound B, in HIV‐infected‐individuals with HAND (Ances et al., 2012 , 2010 ; Clifford et al., 2009 ). Despite this discrepancy in the field, several studies have reported deposition of diffused amyloid depositions in the brains of HAND patients in the post‐cART era and the development of Alzheimer's‐like pathology (Achim et al., 2009 ; Chai et al., 2017 ; Esiri et al., 1998 ; Fields et al., 2020 ; Garces et al., 2023 ; Gelman & Schuenke, 2004 ; Gonzalez et al., 2023 ; Howdle et al., 2020 ; Izycka‐Swieszewska et al., 2000 ; Kim et al., 2013 ; Meehan et al., 2023 ; Nebuloni et al., 2001 ; Raja et al., 1997 ; Stern et al., 2018 ; Xu & Ikezu, 2009 ). There are reports demonstrating that HIV‐1 infected people on anti‐retrovirals, specifically, protease inhibitors, had higher amounts of neurotoxic amyloids and phospho Tau (pTau) levels in the CSF (Fields et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%